Surfactant controlled metal oxide shell layer deposition for enhanced photocatalytic solar hydrogen generation: CdSe/TiO2 nanocomposite a case study - Sudhagar Pitchaimuthu (Materials Letters, 2021)
The present work demonstrates the effect of cationic, anionic and nonionic surfactants on synthesizing nanoscale thin TiO2 shell layer deposited on to pre-synthesized CdSe capsule-like nanoparticles. We benchmark a suitable surfactant for synthesizing homogenous, controlled TiO2 post-deposition onto host 1-D CdSe surface without any complex research tools. Also, we examine the inter-dependence material property and photocatalytic performance in solar hydrogen generation. The generic synthesis of surfactant controlled nanoscale deposition route can transfer to a wide range of semiconductor materials where the surface functional property plays a crucial role.